Trends in frequency and persistence of atmospheric circulation types over Europe derived from a multitude of classifications. (2nd October 2016) - Kučerová, Monika; Beck, Christoph; Philipp, Andreas; Huth, Radan
ABSTRACT: The aim of this study is to quantify changes of atmospheric circulation over Europe using a large number of classifications of circulation types that were collected and developed within the COST733 Action 'Harmonisation and Applications of Weather Types Classifications for European Regions'. Circulation changes over Europe are studied in terms of changing seasonal frequency and persistence of daily circulation types in the period September 1957–August 2002. The extensive collection of both subjective and objective (computer‐assisted) catalogues of circulation types in 12 European domains serves as a platform for comparison of different classification methods, varying numbers of circulation types, sequencing of input sea‐level pressure data, and spatial scale of circulation processes. The overall picture of frequency and persistence trends is consistent with two large‐scale tendencies: strengthening and eastward shift of the North Atlantic Oscillation, and a northwestward shift of storm tracks. There is, however, a limited consistency in the trends between individual classifications. This inconsistency leads us to the recommendation that results of climatological analyses based on a single classification should not be generalized and overinterpreted; it is highly advisable to simultaneously use multiple, and as many as possible, classifications in climatological studies.